An adaptive feedback linearization strategy for variable speed wind energy conversion systems - Valenciaga, Fernando (2000)
This paper presents a control strategy based on adaptive feedback linearization intended for variable speed grid‐connected wind energy conversion systems (WECS). The proposed adaptive control law accomplishes energy capture maximization by tracking the wind speed fluctuations. In addition, it linearizes the system even in the presence of turbine model uncertainties, allowing the closed‐loop dynamic behaviour to be determined by a simple tuning of the controller parameters. Particularly, the attention is focused on WECS with slip power recovery, which use a power conversion stage as a rotor‐controlled double‐output induction generator. However, the concepts behind the proposed control strategy are general and can be easily extended to other WECS configurations.